Internal Audit Effect on Inventory Control: Study at One of The Garment Companies in The City of Bandung - Haifa Khairunisa; Maulana Yusup; Sana Sholihah; Adam Ramdani (Acman: Accounting and Management Journal, 2023)
This research determines the influence of internal audits on inventory control in one of the garment companies in Bandung. This research method uses quantitative research methods with descriptive and verification approaches. First, obtain the questionnaire results from the respondents and then process them through SPSS 20 to be tested and then present the output results. After conducting analysis and discussion, the authors conclude that the effect of internal audit on inventory control carried out at a garment company in the city of Bandung shows quite good results. To see the expertise and accuracy possessed can be obtained from the results of the internal audit. But some are not optimal, which is in the internal audit control, which has not optimally supported the company, so the implementation of audit activities needs to be improved. In addition, the quality assurance program needs to run optimally to support audit performance.